Control of molecular structure in the generation of highly luminescent liquid crystalline perylenebisimide derivatives: synthesis, liquid crystalline and photophysical properties - Jancy, B.; Asha, S. K. (Journal of Physical Chemistry B, 2006)
We report here, for the first time, the role of the molecular design on the liquid crystalline and solid-state photoluminescent properties of soluble and thermally stable liquid crystalline perylenebisimide derivatives. A new series of perylenebisimides were designed and developed for this purpose by adopting the stoichiometry-control approach, and amine-, hydroxyl-, ester-, and amide-functionalized molecules were synthesized. Various types of spacers with different lengths (C2 to C12), types (linear, cyclohexyl, and tricyclodecane), and end-capped by phenyl or tridodecyloxy gallic units were introduced in the perylenebisimide core. The molecules were completely characterized by NMR, FT-IR, SEC, and MALDI-TOF mass techniques. Thermal analysis revealed that the perylenebisimide derivatives were thermotropic liquid crystalline, and threadlike nematic phases were observed under a polarizing light microscope. The spacer length and the rigidity of the spacers play a major role in the liquid crystalline properties of the materials. In phenyl systems, the C6 chain with ester- and the C12 chain with amide-end-capped molecules showed a nematic phase, whereas the C6 chain with an amide end cap and their cyclic and tricyclic counterparts did not show any LC property. The introduction of a tridodecyloxy gallic unit induced the LC property in C12 and the cyclohexyl system; however, it failed to do so in the tricyclodecane molecule. The absorption properties of the molecules were almost unchanged by the structural variation; however, the emission quantum yield in solution and photoluminescent (PL) intensity in the solid state were significantly different. Though the gallic unit induced liquid crystallinity in the perylenebisimide core, the quantum yield and PL intensity are 4−5 times less compared to those of the simple phenyl-capped liquid crystalline system. Among the various types of spacers, the tricyclodecane induced strong molecular aggregates via π-stacking, which in turn increased the rigidity of the entire perylenebisimide core, resulting in the absence of liquid crystallinity and low luminescence compared to their linear and cyclohexyl analogues. The molecular aggregates were very stable even at very dilute concentration and also at high temperatures. The aggregates disappeared immediately upon addition of trifluoroacetic acid, thus confirming the strong hydrogen bonding in the aggregated states. In a nutshell, the present report demonstrates the importance of molecular design for introducing liquid crystalline phases in perylenebisimides and also the development of novel highly luminescent n-type π-conjugated material for application in optoelectronics.

Hydrogen-bonding-induced conformational change from J to H aggregate in novel highly fluorescent liquid-crystalline perylenebisimides - Jancy, B.; Asha, S. K. (Chemistry of Materials, 2008)
A series of highly fluorescent liquid-crystalline perylenebisimide molecules having amide or ester linkage and end-capped by phenyl, monododecyloxy phenyl, or tridodecyloxy phenyl units have been synthesized and fully characterized. The amide-functionalized series self-organized to form H type aggregates regardless of their end-capping in organic solvents like tetrahydrofuran (THF), toluene, and dichloromethane. On the other hand, only the monododecyloxy phenyl end-capped molecule in the ester series showed a tendency to self-organize with a typical J type aggregation in toluene. In both series, the highest aggregation tendency was shown by the one having monododecyloxy phenyl end-capping, with the transition temperature from aggregated to molecularly dissolved species occurring at 60 °C for the amide and 50 °C for the ester molecule. At higher concentrations in toluene, the fluorescence spectra of the monododecyloxy phenyl and tridodecyloxy phenyl terminal-substituted amide derivatives showed the formation of a new peak corresponding to excimer emission at 670 nm. Thin drop cast films of the perylenebisimide ester and amide series gave only excimer emission ∼670 nm upon excitation. Thermal analysis using differential scanning calorimetry (DSC), polarized light microscopy (PLM), and powder X-ray diffraction measurements were utilized to study the liquid-crystalline (LC) characteristics of the molecules. Scanning electron micrograph (SEM) of thin drop-cast samples that were annealed in toluene showed the formation of supramolecular rods several micrometers in length, especially for the amide derivatives. The ester derivative, on the other hand, showed a leaflike morphology thus differentiating it from the amide series, which have both hydrogen bonding and π−π interactions to support self-organization.

Synthesis and self-organization properties of copolyurethanes based on perylenediimide and naphthalenediimide units - Jancy, B.; Asha, S. K. (Journal of Polymer Science Part A-Polymer Chemistry, 2009)
A series of perylene and naphthalene diimide-containing random copolyurethanes with different ratios of perylene/naphthalene diimide content was synthesized and characterized. Copolymerization improved the solubility of these rigid aromatic diimides, and the copolymers were soluble in common organic solvents like chloroform, tetrahydrofuran, and so forth. The absorption spectra of perylene-based copolymers showed a red-shifted peak at a wavelength of 557 nm corresponding to J-type aggregates. For naphthalene copolymers, the quenching of fluorescence at higher naphthalene incorporation suggested the presence of aggregates because of the extensive pi-pi stacking of the aromatic core. FTIR spectroscopic analysis showed that the hydrogen bonding tendency of the polymer decreased with increase in perylene/naphthalene incorporation. The fluorescence spectra of the perylene polymers were exactly a mirror image of the absorption spectra. The fluorescence spectra of the naphthalene polymers at higher naphthalene incorporation showed a red-shifted excimer like emission peak, which was assigned as static excimers based on their excitation spectra. These polymers could exhibit two types of secondary interaction modes, namely, hydrogen bonding (via urethane linkage) and pi-stacking (via aromatic perylene or naphthalene units) thus highlighting the importance of polymer design in inducing self-organization at both low and high incorporation of the rigid bisimide moieties. (C) 2009 Wiley Periodicals, Inc. J Polym Sci Part A: Polyrn Chem 47: 1224-1235, 2009
Keywords: fluorescence; hydrogen bonding; naphthalene diimide polymers; polyurethane copolymer; self-organization; structure-property relations

Structure engineering of naphthalene diimides for improved charge carrier mobility: self-assembly by hydrogen bonding, good or bad? - Kolhe, Nagesh B.; Devi, R. Nandini; Senanayak, Satyaprasad P.; Jancy, B.; Narayan, K. S.; Asha, S. K. (Journal of Materials Chemistry, 2012)
Two families of naphthalene diimide (NDI) derivatives were compared and contrasted for the effect of self-assembly on charge carrier transport. One series of NDI derivatives had a terminal phenyl ring attached to a hexyl spacer substituted naphthalene core either through an ester or an amide linkage (NDI-E and NDI-A, respectively), while the other series had a 3,4,5-tridodecyloxy phenyl unit (NDI-E3, NDI-A3) instead of the terminal phenyl unit. Solution processed thin films of these molecules exhibited n-type charge transport characteristics in a bottom gate top contact organic field effect transistor (OFET) geometry. The amide derivatives showed evidence of self-organization with observation of red shifted aggregate emission in solution as well as solid state. Variable temperature FTIR studies in the solid state confirmed the existence of strong hydrogen bonding which could be broken only at very high temperature. However, contrary to expectations, the NDI ester derivatives showed better device efficiency with electron mobilities in the range 8.5 x 10(-3) to 2 x 10(-2) cm(2) V-1 s(-1) and on/off ratio similar to 10(4). The thin film crystallinity and morphology of NDI-E and NDI-A were examined through X-ray diffraction and atomic force microscopy (AFM). The correlation of crystallinity, hydrogen bonding and charge carrier mobility was studied using energy minimized structures from density functional theory (DFT). The higher electron mobility of ester linked NDI derivatives over the amide linked ones was attributed to the freedom in charge transport pathways offered by a three dimensional crystalline organization in the ester compared to the restricted directional hydrogen bonding interaction in the amide derivatives.